Religious Moderation in the Balinese Diaspora Community on the Island of Lombok - Padli Pawaid Yahya; Ahyunadi (ASTEEC, 2025)
This study aims to explore religious moderation within the Balinese diaspora community in Lombok, influenced by social, cultural, and political interactions between the Hindu Balinese and Muslim Sasak communities. The research method employed is a literature review, analyzing historical sources and academic studies on the relationship between these communities. Despite historical tensions, religious moderation has proven to foster harmony through shared social practices and rituals, such as the Topat War Festival in Lingsar. This study shows that religious moderation not only mitigates conflicts but also strengthens social solidarity amidst religious diversity. This moderation is reflected in daily practices and shared traditions, creating spaces for interfaith dialogue and mutual respect. In conclusion, religious moderation is a crucial element in maintaining social cohesion and harmony in Lombok, serving as a model for multireligious societies in Indonesia.